Culture of Public Vocational Schools (Review of Academic Supervision and Performance) - Bunyamin Bunyamin (Ridwan Institute, 2022)
The research was conducted at a Vocational High School in one of the sub-districts in DKI Jakarta, precisely in Cipayung District with a population of 457 teachers. Using the Kretjie and Morgan Table with an error rate of 0.05, a simple random sample of 207 teachers was taken. Test the hypothesis using a correlation test. Teacher performance variables consist of: ability, motivation, dependability and initiative. Ability indicators are the ability to implement PBM, make lesson plans, use learning media methods and organize school administration. Based on the results of the study, it can be concluded that there is a relationship between the academic supervision of the principal and the organizational culture of SMK Negeri in Cipayung District, East Jakarta. There is a relationship between teacher performance and the organizational culture of SMK Negeri in Cipayung District, East Jakarta. There is a relationship between the principal's academic supervision and teacher performance together with the organizational culture of SMK Negeri in Cipayung District, East Jakarta